Effects of shRNA Targeting Maspin on the Invasion of Extravillous Trophoblast Cell - Shi, Xinwei; Liu, Qing; Liu, Hao; Deng, Dongrui; Qiao, Fuyuan; Wu, Yuanyuan (American Journal of Perinatology, 2017)
Objective Hypomethylation of the maspin gene results in increased expression of maspin in preeclamptic placentas. However, maspin gene function and the molecular aspects in placentation remain largely unclear. The study was designed to investigate the effects of maspin on the invasion of extravillous trophoblast cell line (TEV-1) and the molecular mechanism.Study Design We cloned short hairpin RNA (shRNA) targeting maspin gene into plasmid pGenesil-1.1 eukaryotic expression vector and then transfected it using adenovirus. The methylation rates in the maspin gene were detected by bisulfite sequencing polymerase chain reaction; the invasive ability of trophoblast cells was examined by Transwell chamber assay; the mRNA and protein expression of maspin and some invasive related gene was detected by reverse transcription-polymerase chain reaction and Western blot analysis.Results After the maspin expression was successfully knocked down, the methylation rates in the maspin gene were significantly increased, and the number of cells invading through Matrigel (Corning Life Sciences and BD Biosciences) was obviously increased. The mRNA levels of vascular endothelial growth factor-A (VEGF-A), vascular endothelial growth factor-C (VEGF-C), and matrix metalloproteinase-2 (MMP2) were increased significantly.Conclusion Using shRNA technology, this study further verified that maspin gene methylation could decrease maspin expression and inhibit the invasion of TEV-1 cells through VEGF-A, VEGF-C, and MMP2.
Keywords: shRNA; maspin; trophoblast; preeclampsia; invasion